Expect the unexpected: chronic renal abscess secondary to renal actinomycosis. Issue 12 (16th December 2021) - Walsh, Jennifer; Fennelly, Neil; Kilgallen, Clive; Connor, Eabhann O; Forde, James; Dinesh, Binu; Fitzpatrick, Fidelma
Abstract: Actinomycosis is an invasive infection, which can affect numerous anatomical sites, though rarely the kidney. The rate of nephrectomy is high despite antibiotic therapy. A 51 year old presented with a Proteus mirabilis renal abscess 9 years following a similar renal abscess. The abscess persisted despite appropriate antibiotic treatment and radiological drainage. In addition to P. mirabilis, Actinomyces species was isolated on polymicrobial abscess culture after 6 weeks antibiotic therapy. Despite appropriate antibiotics, nephrectomy was required. Histology confirmed actinomycosis. Actinomycosis should be considered in chronic, destructive infections, especially if failure to respond to appropriate antimicrobials. However, Actinomyces species may be missed by routine culture techniques. Because of the polymicrobial nature of abscesses, good communication with the laboratory is essential to ensure that cultures are prolonged and the isolation of one pathogen does not hinder the isolation of others.